Ecotoxicological assessment of Fluazuron: effects on Folsomia candida and Eisenia andrei - Alves P.R.L. (2019)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. The cattle production in Brazil has increased considerably in the last years, mainly due to the control of parasite infestation of the animals, which cause loss of productivity to the sector. Fluazuron is an active ingredient (a.i.) of the benzoylurea class used to control ticks in cattle. As this a.i. has been found unchanged in animal feces, which may present a risk to edaphic organisms, this study aimed to assess the effects of fluazuron on survival, reproduction, and behavior of the soil invertebrates Folsomia candida and Eisenia andrei, through ecotoxicological assays. We carried out bioassays in a tropical artificial soil (TAS) spiked with increasing doses of the insecticide. Earthworm mortality was found only at the highest tested fluazuron concentration (LOEC = 160 mg a.i. kg −1 dry soil and NOEC = 80 mg kg −1 ), while the reproduction of F. candida and E. andrei was reduced at lower fluazuron concentrations (EC 50 = 4.48 mg kg −1 and EC 50 = 20.8 mg kg −1 , respectively). Avoidance behavior was detected for both species at lower concentrations than those that caused impacts on reproduction, indicating that the substance may affect the soil habitat function. Since the possible adverse effects of fluazuron on edaphic fauna are still unknown or neglected, this study also warns about the possible harmful effect of veterinary pharmaceutical products on edaphic fauna.